Character of Educational Leadership: A Critical Educational Study of Leadership in Local Wisdom - Wayan Agus Gunada, I; Nyoman Harnika, Ni; Kerti Nitiasih, Putu; Wayan Ria Lestari, Ni; Ratna Kamala Sari Lukman, Dwi (KnE Social Sciences, 2024)
This research critiques the practice of educational leadership and explains leadership in Balinese local wisdom. Leadership in schools is the managerial activity of the principal in carrying out the educational process. School management in Bali generally adapts leadership styles in the Western theory. However, is rarely understood in Balinese local wisdom and has the concept of leadership appropriate to socio-cultural conditions and education in Bali. This qualitative research uses data analysis techniques: data reduction, data presentation, and data verification. Based on the research findings, the concept of Balinese local wisdom leadership is full of values and religious character. Balinese local wisdom requires leaders to know their character and to form good leaders’ attitudes and behaviors. In comparison, Geguritan Niti Rajasesana has the concepts of catur pariksa, brata nembelas, and satya, the principle of leading. In the Geguritan Dharma Sesana text, there is a concept of 12 principles for leaders. The concept of leadership does not directly discuss leadership in education but is relevantly integrated into the management of education and organization by school principals in Bali. This study aims to strengthen the concept of educational leadership based on local wisdom and can be a reference for studies related to educational leadership. Keywords: educational leadership, local wisdom, principal, leadership character